Goniometer-apps in hand surgery and their applicability in daily clinical practice. Issue 1 (December 2015) - Kuegler, Paul; Wurzer, Paul; Tuca, Alexandru; Sendlhofer, Gerald; Lumenta, David; Giretzlehner, Michael; Kamolz, Lars-Peter
Abstract Background Smartphones have become an integral part of our daily lives, and numerous applications (apps) make use of the goniometer, which is comparable to a medical protractor. The aim of this study was to evaluate the availability, reliability and validity of medical apps using the goniometer function in smartphones. Methods Sixteen goniometer-apps downloaded from Apple's (twelve apps) and Google's (four apps) app stores matched initial inclusion criteria (inclusion criteria: *gonio* or *rom*, specifically designed to measure angles) were assessed and compared to a universal mechanical goniometer by measuring an irregular, four-sided pyramid with distinct angles. Results Twelve iOS (Apple's operating system) and four Android (Google's operating system) apps were included. Ten of twelve iOS apps were showing an average deviation from the real angles of a maximum 1.8°; the values for Android apps did not exceed 1.3°. Conclusions Fourteen out of sixteen apps were reliable and valid for measuring angles. Based on correct handling and adequate user-applicability of the on-board goniometer these apps can make a smartphone applicable for data acquisition in medicine. So far, smartphone apps for measuring angles have not been readily applied in clinical practice in hand surgery.